Mortality and Morbidity in Infants <34 Weeks' Gestation in 25 NICUs in China: A Prospective Cohort Study - Siyuan Jiang; Weili Yan; Shujuan Li; Lan Zhang; Yi Zhang; Prakesh S. Shah; Prakesh S. Shah; Vibhuti Shah; Vibhuti Shah; Shoo K. Lee; Shoo K. Lee; Shoo K. Lee; et al. (Frontiers Media S.A., 2020)
Objectives: To describe the rates and variability of mortality and morbidity of preterm infants born in China.Methods: This prospective cohort study included infants born at <34 weeks' gestation and admitted to 25 NICUs within 7 days of birth between May 1st, 2015 and April 30th, 2016. Infants were followed until death or NICU discharge. The primary outcome was a composite of mortality or any major morbidity (sepsis, necrotizing enterocolitis, intraventricular/periventricular leukomalacia, retinopathy of prematurity, and bronchopulmonary dysplasia) in infants who received complete care following medical advice. Secondary outcomes included rate of discharge against medical advice, mortality and individual morbidities.Results: Of the 8,065 infants, 6,852 (85%) received complete care and 1,213 (15%) were discharged against medical advice. Among infants who received complete care, the rate of the composite outcome was 27% (1,827/6,852), mortality 4% (248/6,852), sepsis 14% (990/6,852), necrotizing enterocolitis 3% (191/6,550), intraventricular hemorrhage/periventricular leukomalacia 7% (422/6,307), retinopathy of prematurity 2% (67/3,349), and bronchopulmonary dysplasia 9% (616/6,852). There were significant variations between NICUs for all outcomes.Conclusions: Discharged against medical advice, mortality, and morbidity rates for preterm infants <34 weeks' gestation are high in China with significant variations between NICUs.